Sustainability, stakeholder governance, and corporate social responsibility - Dorobantu, Sinziana; Aguilera, Ruth V.; Luo, Jiao; Milliken, Frances J. (Emerald Publishing Limited, 2018)
Scholarly interest in the areas of sustainability, stakeholder relations and corporate social responsibility (CSR) has increased considerably in recent years. In this volume, we take a step back to consider the fundamental questions that underlie and tie research across these areas together. The chapters in this volume cover a wide range of theoretical perspectives grounded in strategy, economics and sociology, employ various methodological approaches, and offer new arguments on the connections that exist between firms decisions relating to sustainability, CSR, and the governance of their stakeholder relations. The chapters in this volume highlight that business decisions relating to sustainability and CSR are ultimately decisions about the governance of stakeholder relations, and suggest that future work in these areas should consider more closely both the firms and their stakeholders as strategic actors driving firm decisions.- Resumé vydavatel
Includes index.
Keywords: řízení a správa společností; společenská odpovědnost firem; environmentální odpovědnost; corporate governance; corporate social responsibility; environmental responsibility; elektronické knihy; sborníky; electronic books; papers of several authors